Efficacy and tolerance of cetuximab in combination with 5 FU plus irinotecan based chemotherapy in metastatic squamous cell anal carcinoma. Issue 3 (March 2023) - Valery, M.; Cervantes, B.; Smolenschi, C.; Boilève, A.; Boige, V.; Malka, D.; Hollebecque, A.; Ducreux, M.
Abstract: Background: Squamous cell anal carcinoma (SCAC) is an uncommon neoplasia often cured by surgery and/or chemo-adiation therapy at the localized stage. Although the first-line treatment for metastatic anal canal cancer is now better codified with two validated treatment regimens, carboplatin-paclitaxel and modified docetaxel-cisplatin-5FU (DCF), there is little data and no consensus regarding subsequent lines [1–5] . In this study, we report the safety and efficacy of cetuximab (an epidermal growth factor receptor inhibitor) in combination with 5-FU plus irinotecan based chemotherapy. Method: A retrospective analysis of patients with metastatic SCAC (mSCAC), who failed on at least one prior line of treatment, before being treated with the combination FOLFIRI and cetuximab between March 2015 and February 2022 at Gustave Roussy cancer center, was performed. Results: A total of 33 patients with a pre-treated mSCAC were analyzed. The combination of FOLFIRI and cetuximab provided a disease control rate (DCR) of 73%, and response rate of 30%. With a median follow-up of 38 months, the median progression free survival was 5.5 months, and the median overall survival was 13.7 months. Fourteen patients (42%) experienced grade III/IV adverse events that remained manageable. Conclusion: Our study suggests that FOLFIRI and cetuximab is a promising combination in the management of mSCAC with a very good DCR and a manageable toxicity profile. Further prospective trials would be needed to confirm our results.